Approach to the increase of systematic effectiveness of the complex "Crew - Airplanes - Medium" - Воробьев, В. М. (Proceedings of National Aviation University (archive), 1998)
Worked out and broadly discussed on the basis of modern understanding of reliability of complex systems is new concept of increasing effectiveness of final link of safety of flights "Crew - Airplanes - Medium". The concept is based on the methodology of systematic approach, on modern information technologies on generalization of the experience of maintenance of avionics on the basis of integral modual design and normative technical documentation